LINGUOCULTURAL FEATURES OF TOPONYMS IN ENGLISH AND UZBEK - A.X. Kurbonov; M.Ch.Abdusalomova (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article studies the linguocultural features of toponyms in English and Uzbek. The focus is placed on the way place names carry history, social memory, local identity, and emotion. Recent studies on toponymy are used together with short literary extracts from Jane Austen’s Pride and Prejudice and Abdulla Qodiriy’s O‘tkan kunlar. Descriptive, comparative, contextual, and linguocultural methods are applied. The analysis shows that English literary toponyms often mark estate culture, rank, and social space, while Uzbek literary toponyms often reflect craft life, regional identity, and historical tension. It is also shown that a toponym may work as a small cultural text. The article may be useful for students of linguistics, translation, literary studies, and cultural studies.